2021
DOI: 10.1126/scitranslmed.abb5071
|View full text |Cite
|
Sign up to set email alerts
|

A resident stromal cell population actively restrains innate immune response in the propagation phase of colitis pathogenesis in mice

Abstract: Inflammatory bowel disease (IBD) affects 0.3% of the global population, yet the etiology remains poorly understood. Anti-inflammation therapy has shown great success, but only 60% of patients with IBD benefit from it, indicating that new targets are needed. Here, we report the discovery of an intrinsic counter regulatory mechanism in colitis pathogenesis that may be targeted for IBD treatment. In response to microbial invasion, resident Vimentin+ stromal cells, connective tissue cells genetically marked by Twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…PTGS2, alternatively termed COX-2, is an inflammatory enzyme associated with intestinal inflammatory disease like IBD ( 34 ). A previous clinical study has demonstrated a negative correlation between the protein levels of COX-2 and the disease severity of IBD ( 35 ). A review has also suggested that COX-2 can cause the clinical manifestations of a bacterial infection, including inflammation and septic shock ( 36 ).…”
Section: Discussionmentioning
confidence: 95%
“…PTGS2, alternatively termed COX-2, is an inflammatory enzyme associated with intestinal inflammatory disease like IBD ( 34 ). A previous clinical study has demonstrated a negative correlation between the protein levels of COX-2 and the disease severity of IBD ( 35 ). A review has also suggested that COX-2 can cause the clinical manifestations of a bacterial infection, including inflammation and septic shock ( 36 ).…”
Section: Discussionmentioning
confidence: 95%
“…Recent epidemiological statistics indicate that the incidence of UC continues to increase worldwide, now affecting 0.3% of the global population (28). Therefore, it is particularly urgent to develop natural medicines with low side effects and proven safety.…”
Section: Discussionmentioning
confidence: 99%
“…However, this signaling change may result in other unexpected effects such as anti-angiogenesis and anti-tumorigenesis, as was reported in a previous study [ 1 ], and should be investigated in greater detail in the future. In addition, the DSS was used to produce a mouse IBD model following previous studies [ 30 ]. Other reagents such as polyinosinic-polycytidylic acid and 2,4,6-trinitrobenzene sulfonic acid could be used to exert the same pathogenic effects and thereby produce rodent IBD models [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%